Anti-HBV neonatal immunization with recombinant vaccine. Part II. Molecular basis of the impaired alloreactivity - Martinetti, M.; Cuccia, M.; Daielli, C.; Ambroselli, F.; Gatti, C.; Pizzochero, C.; Belloni, C.; Orsolini, P.; Salvaneschi, L. (Vaccine, 1995)
HLA study was performed in 9 absolute non-responder (serum titre of anti-HBsAg < 2 mIU ml −1) and 8 hyporesponder (serum antibody level between 2 and 9.9 mIU ml −1) babies who underwent, in neonatal period, HBV vaccination with Engerix B recombinant vaccine. The investigation pointed out that many of these subjects carry HLA haplotypes classically involved in autoimmune diseases: namely HLADR7;DQ2, DR4;DQ8 and DR3;DQ2. The genomic typing for DRB1, DRB3, DRB4, DRB5, DQA1, DQB1 and DPB1 genes revealed an increased frequency of the DRB1 ∗0701; DQA1 ∗0201; DQB1 ∗0201 haplotype (23.5 vs 9.9% of the controls) and of DPB ∗0201 allele (42.3 vs 13.2% of controls). The polymorphism of Bf, C4A and C4B complement serum components, recognized as important “immune-function-related genes”, pointed out an increased frequency of the null allele C4AQ0 (34.3 vs 6.8% of the controls) stressing the role of C4A serum complement component in response to foreign peptide. The immunogenetic investigation has been extended to 23 responder babies (titre of anti-HBsAg > 50 mIU ml −1), vaccinated with the same trial as the poor responders. The HLA frequencies observed in this group were comparable to those of control population and, with respect to the HLA markers cited above, absolutely different from the non/hyporesponder infants. From the HLA class II sequence analysis in the group of poor-responder babies some characteristics, peculiar to autoimmune diseases, have been observed: the majority of the infants showed at least an arginine at the 52 residue of the α chain of DQ molecule and a non-aspartic acid at the 57 position of the DQβ chain. These data highlight that the impaired responsiveness to HBV vaccination is able to select children sharing the immunogenetic background of people prone to autoimmune conditions.